Esophageal Stenosis due to Exogenous Chemical Injury - Ubilluz Dhaga del Castillo, Rodrigo (1963)
Erosive esophagitis in 34 dogs was produced by instillation transesofagoscópica commercial bleach or sodium hydroxide solutions and existing lesions at 13, 21 and 30 days duration was studied. In 8 animals the spontaneous evolution of corrosívcs esophageal lesions , verifying abundance of young fibroblasts , incipient fibrosis and occlusive vascular lesions to the second week of aggression was analyzed. Between 21 and 35 days fibrosis had been outstanding . 14 dogs were divided into three subqrupos and violated with sodium hydroxide solutions of increasing concentrations ( 2.5 N, 5 N and 10 N ) . The immediate mortality was very high in all three subqrupos . The severity of the inflicted damage increased as a direct function of the concentration of the corrosive agent , showing that any clinical or therapeutic assessment should consider the influence of this factor . No favorable effect of parenteral chymotrypsin was observed in the group of animals subjected to the previous experience. Intramuscular administration of adrenocorticotropic hormone to 9 animals allowed to observe rapid attenuation of dysphagia and the healing process , without stenosis removed . Moreover, this group recorded the largest number of micro - perforations and abscesses of the etched walls. ACTH action was similar to that described for the adrenocortical hormones.